PERBEDAAN TINGKAT KESUKAAN DAN DAYA SIMPAN KUE BAY TAT DENGAN SUBSTITUSI TEPUNG SUKUN - Dzikrillah, Athiffa; Elida, Elida; Kasmita, Kasmita; Holinesti, Rahmi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract : This study was motivated by previous research on Bay Tat cake with 50% breadfruit flour substitution, which showed the best results based on organoleptic tests. The purpose of this study was to determine the differences in preference levels and shelf life of Bay Tat cake between the two treatments. This research used a mixed method with a qualitative approach through shelf-life observation and a quantitative approach through a hedonic test by 50 untrained panelists on the attributes of color, aroma, taste, and texture. Hedonic test data were analyzed using the Paired Sample T-Test with a t-table significance limit of 1.976 (α = 0.05; df = 149). The results showed significant differences between the control and 50% breadfruit flour substitution in aroma (t = 4.630 > 1.976), taste (t = 2.588 > 1.976), and inner texture (t = 3.713 > 1.976). Meanwhile, outer color (t = –1.313 < 1.976), inner color (t = 0.315 < 1.976), and outer texture (t = –1.164 < 1.976) showed no significant differences. Shelf-life observation showed that both treatments had the same shelf life, lasting up to the 5th day at room temperature (27–30°C), after which quality deterioration began to occur.Keywords: Bay Tat, Beadfruit Four, Hedonic Test, Shelf Life.